Efecto de la concentración de lecitina de soya (Glycine max) y harina de kiwicha (Amaranthus caudatus) en la evaluación en barras personalizadas con chocolate elaboradas con impresión 3D - Tapia Celis, Jean Pieree (2019)
The purpose of this research was to make a chocolate bar with flour from kiwicha (Amaranthus caudatus) and soy lecithin (Glycine max) using 3D printing technology. A conventional 3D printer (used to print with plastic) was used to which the extrusion system was modified to "print" custom bars. Free softwares were used to design new parts (Repetier Host), commands (Arduino) and circuits (Fritzing) in the construction of the new extruder. PLA plastic was used to build the parts that allowed the extruder to be assembled in the conventional 3D printer. Different concentrations of kiwicha flour (10%- 30%) and soy lecithin (0% - 10%) were used to make the chocolate bar, completing 100% with milk chocolate; following an experimental design of the type 22 + 2 * 2 + 4 center points. A sensory evaluation was performed with a hedonic scale of 7 points and categorical responses were obtained. For processing responses, it was worked by modeling of ordinal logistic regression, obtaining coefficients for each factor with category changes, obtaining values that indicate the probability of liking a product with a 95% confidence level. For the statistical processing the R software was used. The result of this analysis was that the chocolate bar personalized with 3D printing was more likely (79%) to be accepted with high liking by consumers possessed in its composition 20% of kiwicha flour ang 5% of soy lecithin. The physicochemical characteristics of this chocolate bar were, red (223.75), green (202) and blue (176.5), humidity expressed on a wet basis 2.09±0.22 an pH 5.43±0.39, which identifies it as a chocolate bar with characteristics similar to a commercial chocolate.